Pengaruh Komunikasi Pemasaran Dalam Kesuksesan Bisnis di Toko Kelontong Seroja Perawang - Lidya Mutiara Hutasoit; Lenti Susanna Saragih; Dany Ajar Baskoro (Student Scientific Creativity Journal, 2024)
This research aims to determine the influence of marketing communication on business success at the Seroja Perawang Grocery Store. The research method used is a descriptive method with a qualitative approach. Data collection techniques are carried out through interviews, observation and documentation. The research results show that marketing communication has a significant influence on business success at the Seroja Perawang Grocery Store. This is proven by increased sales, brand awareness and customer loyalty after implementing an integrated marketing communications strategy.